2016
DOI: 10.1186/s12868-016-0291-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34b mediates hippocampal astrocyte apoptosis in a rat model of recurrent seizures

Abstract: BackgroundRecurrent convulsions can cause irreversible astrocyte death, impede neuron regeneration, and further aggravate brain damage. MicroRNAs have been revealed as players in the progression of numerous diseases including cancer and Alzheimer’s disease. Particularly, microRNA has been found linked to seizure-induced neuronal death. In this study, a rat model of recurrent convulsions induced by flurothyl treatments was utilised to assess the alterations of microRNA expressions in hippocampus tissues. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
21
0
3
Order By: Relevance
“…Prostaglandins such as PGD2 and PGE2 have been revealed to exacerbate hypoxic injury in neurons [30]. Moreover, several miRs have recently been reported to be associated with hypoxia and ischemia [31, 32] and to have protective roles in neuron damage, such as miR-34b-5p expression in astrocytes [33] and miR-210 downregulation of glucocorticoid receptor protein, and in the neonatal brain in response to HIBD [9]. Importantly, the miR-592 level has also been reported to decrease after cerebral ischemia, and miR-592 overexpression decreases ischemic injuries in neurons [34].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins such as PGD2 and PGE2 have been revealed to exacerbate hypoxic injury in neurons [30]. Moreover, several miRs have recently been reported to be associated with hypoxia and ischemia [31, 32] and to have protective roles in neuron damage, such as miR-34b-5p expression in astrocytes [33] and miR-210 downregulation of glucocorticoid receptor protein, and in the neonatal brain in response to HIBD [9]. Importantly, the miR-592 level has also been reported to decrease after cerebral ischemia, and miR-592 overexpression decreases ischemic injuries in neurons [34].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that up‐regulation of the nuclear factor of kappa B (NF‐κB) pathway can promote anti‐apoptosis of cells under oxidative stress . Bcl‐2 protein has been thought of as an anti‐apoptotic protein . Therefore, we evaluated the anti‐apoptotic effect of NF‐κB pathway activation in MSCs under oxidative stress, with Bcl‐2 as an indicator.…”
Section: Introductionmentioning
confidence: 99%
“…The single miR reported changed in four studies, miR-34b, was increased in all four, suggesting it may play an important role. Mir-34b is interesting as it plays a role in brain development [92] and in Parkinson’s disease [93] as well as regulating apoptosis of astrocytes in the setting of seizures [94]. Of 79 miRNAs reported changed in two studies, 44% reported the same direction of change (increased or decreased) in both.…”
Section: Discussionmentioning
confidence: 99%